Peranan Keluarga, Sekolah dan Masyarakat dalam Pendidikan Islam: Pengembangan Bakat Minat Anak - Silahuddin Silahuddin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2017)
Education will work well if supported by all aspects of education that includes family, community and school. All three are aspects that can not be mutually interconnected with each other. Parents are the first most responsible parties in developing talents and interests of children, then the children's education will be directed through professionals who are in the school environment, and in the community.